Comparasion Of Levels Perbandingan Kadar Flavonoid Ekstrak Daun Karet Kebo (Ficus elastica)Hasil Ekstraksi Bertingkat Menggunaka - evatiara, nur; Suhaenah, Asriani; Tahir, Masdiana (PHARMACY UMI JOURNAL SYSTEM, 2024)
NUR EVATIARA. Comparison of flavonoid levels of rubber plant leaf extract (Ficus elastica) resulting from multilevel extraction using the UV-Vis spectrophotometric method. (Supervised by Asriani Suhaenah and Masdiana Tahir). Rubber plant (Ficus elastica) is a plant in the Moraceae family whose leaves have been empirically stated to contain secondary metabolite compounds such as saponins, polyphenols, flavonoids and tannins which have been used as medicine for coughing up blood, improving urine flow, relieving pain and improving blood circulation. The aim of this research was to determine the comparison of levels of flavonoid compounds in rubber plant leaf extract (Ficus elastica) resulting from multilevel extraction using the UV-Vis spectrophotometric method. The multistage extraction process uses 3 different types of solvents, namely n-hexane (nonpolar), ethyl acetate (semipolar), and ethanol (polar) using a sonicator. Determination of flavonoid levels using the UV-Vis spectrophotometric method, with a maximum wavelength of 432 nm and quarcetin as a comparison. The research results were influenced by the solvent used in comparing the levels of flavonoid compounds, namely rubber plant leaf extract (Ficus elastica) with a multilevel extraction method, namely N-hexane extract 7.161 mgQE/g, Ethyl acetate extract 7.663 mgQE/g, 96% Ethanol extract 10.592 mgQE/g g.